Laparoscopic Single Anastomosis Sleeve Ileal Bypass with Follow-up of Weight Loss and Metabolic Impact - Abdalaziz, Ahmad; Sarhan, Mohamed D.; Abou-Eisha, Hesham Ahmed; Abdelsalam, Ahmed; Saqr, Ahmed; Fathy, Ehab (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Bariatric surgery has been an effective safe management for severe obesity. The newly developed single-anastomosis sleeve ileal (SASI) bypass has shown efficacy as a functional as well as mechanical restrictive bariatric procedure, with a neuroendocrine modulation effect. SASI bypass is still an investigational procedure, hence, more evidence is needed till it is declared as a standard bariatric procedure by the IFSO. Aim of the study: The current work aimed to describe our experience regarding the technical steps, the efficacy and the short-term outcome of SASI bypass procedure in patients with severe obesity. Patients and methods: Forty seven patients with severe obesity underwent SASI bypass procedure. They were followed till 1 year postoperatively. The weight loss, comorbidities and laboratory changes were assessed. Results: Patients evaluation at the 1-year postoperative follow up revealed a mean %TWL of 37.55 ± 6.17 and a mean %EBWL of 76.21 ± 9.8. The remission rates of T2DM, hyperlipidemia and hypertension were 85.7%, 94.7% and 89.66%, respectively, with statistically high significant differences between the preoperative and 1-year postoperative comorbidities rate. Stepwise regression analysis demonstrated that only the preoperative HbA1C remained in the model predicting the %TWL, and the preoperative BMI was the remaining factor in the model predicting the %EBWL in the study patients. Conclusion: The present study adds a new evidence to the promising outcome of the newly introduced SASI bypass procedure. After one year, the study patients showed excellent weight loss and comorbidities remission together with acceptable major complication rates.